Development and Application of 3D Visualization Platform for Flood Evolution in Le'an River Basin of Wuyuan. Issue 1 (February 2021) - Yang, Bin; Ma, Jianming; Huang, Guoxin; Cao, Daling
Abstract: With the rapid development of computer network technology, virtual display technology has become a typical representative of modern information technology, which can provide more efficient and intuitive technical means for flood prevention and risk assessment of water conservancy departments, and make more innovations and breakthroughs in the field of 3D simulation. This paper takes the area of Wuyuan County in the upper reaches of Le'an River in Poyang Lake as an example. Based on WebGIS technology, spatial database technology, CTS virtual display technology and combined with TOPMODEL semi-distributed hydrological model and IFMS domestic flood analysis software, it uses computer languages such as C#.NET and Java to carry out secondary development, explore and build a three-dimensional immersive hydrological multi-element virtual reality platform with real-time interactive display function, and realize the dynamics simulation display of three-dimensional data query, water and rain monitoring, flood evolution, submergence analysis, disaster assessment and other scenes under the three-dimensional perspective. It also provides an auxiliary decision-making platform for flood control and disaster reduction in the river basin, and further improves the guarantee level of water safety in the river basin.